Sodium intake assessed by 24-h urine excretion and its relationship with anthropometric measurements in Malaysian adults - Syafinaz Mohd Sallehuddin; Rashidah Ambak; Fatimah Othman; Nur Shahida Abd Aziz; Lalitha Palaniveloo; Noor Safiza Mohd Nor; Rasidah Jamaluddin; Azli Baharudin; Nor Azian Mohd Zaki; Mohamad Hasnan Ahmad (BMC, 2021)
Abstract Background Sodium intake is associated with anthropometric measurement including weight, waist circumference (WC), and body mass index (BMI). Higher intake of sodium is usually linked to higher risk of obesity among adults globally, especially in developing countries. This study aims to explore the probable relationship between sodium intake by 24-h urine excretion assessment and anthropometric measurement of adults in Malaysia. Methods A cross-sectional study was conducted from October 2017 to March 2018 using a multi-stage stratified sampling method among Malaysian adults aged 18 years old and above. Sodium intake was determined by 24-h urinary sodium excretion, estimated from the respondents' 24-h urinary sample. Height was obtained based on standard protocol. Weight and WC were measured twice using validated anthropometric equipment and BMI was calculated according to World Health Organization (WHO) 1998 classification. Descriptive analysis was done to describe socio-demographic characteristics. A simple linear regression and multiple linear regression tests were done to assess the relationship of 24-h urinary excretion and anthropometric measurement. All statistical analysis was done using SPSS version 22.0. Results Of 1047 interviewed respondents, 798 respondents had done the 24-h urine collection (76.0% response rate). Majority was between 40 and 59 years old (43.5%) and married (77.7%). Simple linear regression showed a significant positive linear association between 24-h urinary excretion and household income, WC, and obese group. In the multivariate analysis, it was indicated that, an increase of 1 unit of BMI will significantly increase the sodium intake by 129.20 mg/dl and an increase of 1 cm of WC will significantly increase the sodium intake by 376.45 mg/dl. Conclusion Our study showed a positive significant relationship between sodium intake estimated by 24-h urinary sodium excretion and BMI of Malaysian adults. More research is suggested on how sodium control can potentially contribute to obesity prevention.